Improving Environmental Awareness through Conservation Education at SD Inpres Naikoten I: Peningkatan Kesadaran Lingkungan melalui Pendidikan Konservasi di SD Inpres Naikoten I - Pramatana, Fadlan; Marimpan, Lusia Sulo; Purnama, Maria M. E.; Mau, Astin E.; Sinaga, Pamona Silvia; Sipayung, Roni Haposan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Urban area development is the main goal in supporting the community economy. However, urban development often harms the environment. Human resources increasing, if not balanced with environmental awareness, will potentially cause problems in the future. Increasing ecological awareness needs to be done from an early age so that the benefits and impacts of human activities on the environment can be understood. This service activity aims to improve environmental awareness and provide knowledge about ecological love and the benefits of the environment. This service activity was carried out in two stages: delivering material using the environmental game and the evaluation stage. SD Inpres Naikoten I students received the program well, as seen from their activeness and enthusiasm when delivering the material. Students are also active in discussions and provide opinions at the evaluation stage. The teachers accompanied the students during the program's implementation and felt helped by the game media, which could be used sustainably